Influence of Leadership Style and Work Environment on Employee Performance (Case Study at Employee PT Astra International Tbk – Auto 2000 Sisingamangaraja Medan) - Ari Priatmojo Seno; Febby Melany; Daud Arifin (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to determine